A DEMOCRACIA ATENIENSE E NÓS - José Antonio Dabdab Trabulsi (Centro Universitário de Belo Horizonte, 2017)
eoi/doi Deposit-Electronic Object Identifier http://eoi.citefactor.org/10.11248/ehum.v9i2.2144 THE ATHENIAN DEMOCRACY AND US THE MODERNS, AND ANCIENT ATHENIAN DEMOCRACY.